A review of flood mitigation benefit-cost analyses’ inclusiveness of environmental watershed effects and environmental vulnerability: gaps in progress towards more resilient flood hazard decision-making - Akhter, Fahmida; Bastola, Sapana; Penn, Jerrod; Douthat, Thomas (Frontiers in Built Environment, 2025)
US and EU flood mitigation policy both incorporate considerations of costs and benefits, and in recent years have taken steps to encourage accounting for positive and negative effects on vulnerable populations, broader non-market environmental impacts, and downstream effects beyond the target area of projects of flood mitigation projects. This work highlights the extent to which previous academic flood mitigation Benefit-Cost Analyses (BCA) papers have comprehensively considered such project effects. We do so through a systematic, PRISMA-style, review of BCA literature in the broader field of flood hazard mitigation and resilience decision-making. Our results suggest 1) most projects focus on monetizing property damages, 2) a gap exists monetizing ecosystem and environmental effects (especially linked to model-linked effects estimates), and 3) almost no BCA literature addresses distributional or economic or social vulnerability related impacts. Studies comprehensively incorporating structural, environmental, and distributional questions are almost nonexistent. This reflects the need for a larger research approach linking flood depth and exposure models to wider non-property and non-market damage assessment. Current BCA literature fails to wholistically bring together the relevant interdependent social and environmental effects of flood mitigation projects. This suggests the need for a research agenda promoting the consolidation of methods beyond traditional property damages, and models linking the environmental and distributional effects of mitigation projects.